2016
DOI: 10.1186/s13071-016-1732-x
|View full text |Cite
|
Sign up to set email alerts
|

Eco-epidemiology of porcine trypanosomosis in Karim Lamido, Nigeria: prevalence, seasonal distribution, tsetse density and infection rates

Abstract: BackgroundAnimal trypanosomosis is a major economic disease in Nigeria causing considerable morbidity and mortality in livestock. Despite reports in other animals, the disease is under reported in pigs.MethodsWe conducted a community based epidemiological study on African animal trypanosomosis in Karim Lamido area of Taraba State, Nigeria using species-specific PCR on 712 pigs and 706 of the 2822 captured tsetse flies. Data were analysed using Chi-square, odds ratio and multivariate analysis at 95 % confidence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 28 publications
2
9
0
Order By: Relevance
“…The Tc infection rates in our study were high in G. pallidipes and G. m. morsitans; for the latter tsetse fly species, a study in Malawi reported a high prevalence for T. brucei (64.4%) but much lower for all other Trypanosoma infections(< 10%) 58 . The mixed infection of Trypanosoma species/subspecies is in agreement with previous reports 35 , 52 , 57 , 59 .…”
Section: Discussionsupporting
confidence: 93%
“…The Tc infection rates in our study were high in G. pallidipes and G. m. morsitans; for the latter tsetse fly species, a study in Malawi reported a high prevalence for T. brucei (64.4%) but much lower for all other Trypanosoma infections(< 10%) 58 . The mixed infection of Trypanosoma species/subspecies is in agreement with previous reports 35 , 52 , 57 , 59 .…”
Section: Discussionsupporting
confidence: 93%
“…The global results obtained with BCT, TL and PCR confirmed high trypanosome infection rates in pigs as already observed in previous studies conducted on the neighboring Bonon and Sinfra HAT endemic foci [11,39] or in other study areas in West and Central Africa as in Nigeria [40], Chad [41] or Cameroon [42][43][44]. Such high infection rates in pigs may be linked to their tolerance to trypanosomes as already observed in the field [20] or during experimental infections with T. b. gambiense [45], and certainly illustrate that the pig is a preferential host for tsetse flies [46,47].…”
Section: Plos Neglected Tropical Diseasessupporting
confidence: 87%
“… Forest plot of the prevalence estimates of trypanosome-infected tsetse flies in Nigeria between 1960–2017 [ 26 , 29 , 40 , 42 , 49 , 59 , 100 , 106 – 112 ] …”
Section: Resultsmentioning
confidence: 99%